The Impact of Foreign Direct Investment on Profitability of Domestic Firms in the UK - Deng, Xiang (2007)
With the advent of globalization, there has been an increasing trend for the development of FDI since the mid-1980s. The host country can not only benefit from FDI as a source of external capital, but also can benefit through the technology transfer and technological spillover effects. In the previous literature, some researchers concentrate on studying the effects of FDI on the economic performance indicators, while others focus on examining the impacts of FDI on the firms.